The Profile of Efl Learners As Measured By An English Proficiency Test - Sulistyo, Gunadi Harry; Suharyadi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2018)
This study aims at profiling the students’ English proficiency in the Department of English, Universitas Negeri Malang (UM). The English proficiency of 277 students across admission Classes in 2016, 2015, 2014, and 2013 who are involved in the study is measured by using a proficiency test. The subtests reliability was assured and the data was analyzed by using descriptive and inferential statistical analyses. The results show no respondent reached the advanced level; the majority was in the low intermediate level. It indicates that the respondents’ score was not linear with their year of admission classes. However, a linearly increasing average score was respectively observed from the scores of Classes of 2015, 2014, and 2013. Statistical differences in the mean scores of the students across admission classes were observed. Next, no evidence of statistical differences was observed in the mean score of the students across different study programs in their seventh semester. Finally, none of Class of 2013 exactly met the graduate profile. However, those beyond the profile and those below the profile were marginally comparable. These findings were further discussed.